Micro Versus Macro – The Effect of Environmental Confinement on Cellular Nanoparticle Uptake - Damle, Viraj G.; Sharmin, Rokshana; Morita, Aryan; Nie, Linyan; Schirhagl, Romana (Frontiers in Bioengineering and Biotechnology, 2020)
While the microenvironment is known to alter the cellular behavior in terms of metabolism, growth and the degree of endoplasmic reticulum stress, its influence on the nanoparticle uptake is not yet investigated. Specifically, it is not clear if the cells cultured in a microenvironment ingest different amounts of nanoparticles than cells cultured in a macroenvironment (for example a petri dish). To answer this question, here we used J774 murine macrophages and fluorescent nanodiamonds (FND) as a model system to systematically compare the uptake efficiency of cells cultured in a petri dish and in a microfluidic channel. Specifically, equal numbers of cells were cultured in two devices followed by the FND incubation. Then cells were fixed, stained and imaged to quantify the FND uptake. We show that the FND uptake in the cells cultured in petri dishes is significantly higher than the uptake in a microfluidic chip where the alteration in CO2 environment, the cell culture medium pH and the surface area to volume ratio seem to be the underlying causes leading to this observed difference.